RECONTEXTUALIZING CLASSICAL PHILOSOPHY IN ISLAMIC PUBLIC SPHERE: FAHRUDDIN FAIZ’S NGAJI FILSAFAT AS A POSTMODERN PEDAGOGICAL PRACTICE - Mustamin, Kamaruddin; Muhammad Alwi HS, (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2026)
This research examines how classical philosophy is recontextualized within the Islamic public sphere through Ngaji Filsafat study sessions led by Fahruddin Faiz. The phenomenon is analyzed as a form of postmodern pedagogy that renegotiates the boundaries between Islamic tradition and rational-philosophical thought. Using a qualitative approach, the study explores how the values and concepts of classical philosophy—such as the ideas of Socrates, Plato, Aristotle, Al-Ghazali, Ibn Sina, and others—are presented in a lecture format that resonates with urban Muslim communities. The findings reveal that Ngaji Filsafat serves as an alternative space of articulation, blending spirituality, rationality, and critical reflection in a fluid, inclusive, and context-sensitive manner. This reflects a new dynamic in contemporary religious practices, one that challenges the dichotomy between faith and reason while opening new possibilities for philosophical education in Muslim societies. The study concludes that the recontextualization of classical philosophy is not only feasible within the Islamic public sphere but also flourishes through non-traditional, dialogical, and deconstructive pedagogical approaches.